Identification of Causes Leading towards Spreading Dropout of Primary School Students in District Sukkur - Shahabuddin, Hafiz; Zafar, Jam Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The study entitled, “Identification of Causes Leading towards Spreading Dropout of Primary School Students in District Sukkur.” The study was survey and descriptive in nature. The quantitative approach was used for data analysis. The explanatory sequential technique was adopted for the study. Population of the study head teachers, primary school teachers, parents of dropout students studying in primary classes. The stratified random sampling was applied for data collection. Sample of the study consisted of sixty four (64) head teachers, one hundred and ninety two (192) primary school teachers and sixty four (64) parents of students. The researcher personally visited and collected the data. The collected data was analyzed through SPSS-24 using relevant statistical formulas as frequency, percentage, standard deviation, mean etc. Findings of study showed that the basic and primary schools are the most ignored sector in Sindh. The shortage of funds for primary schools and poor management are basic reasons. The political interruption is one of the major factors leading to exploitation; liking and disliking of authorities, poor educational quality. The interaction and collaboration is poor especially at primary school level is the reason of less admission rate and rising students’ drop-out rate. The shortage of resources for teachers’ training and lake of other facilities are causes of parents’ confusion; difficulties in admission process and students’ leave ratio from primary classes. The education policies, rules and processes to discourage the mismanagement from primary education.